PROBLEM IDENTIFICATION OF DOMESTIC WWTP OFFICE BUILDING AND ALTERNATIVE TO OVERCOME THEM (CASE STUDY : PT. USAHA GEDUNG BDN, JAKARTA) - Petrus Nugro Rahardjo; Wahyu Widayat (Jurnal Rekayasa Lingkungan, 2016)
In general, the main problem of domestic wastewater treatment plant (WWTP) for office buildings in Jakarta is the incompatibility between the surface load of wastewater and the capacity of WWTP. At the beginning a capacity of WWTP is already predetermined and corresponding to the rate of wastewater generated. But because of the demands of the means for the benefit of various business, so that the capacities of the office building should be developed. This case occurred on PT. Usaha Gedung BDN. Four environmental parameters, namely TSS, Ammonia, Grease & Oil and COD, produced from the WWTP still exceeded the allowable quality standards. Therefore PT. Usaha Gedung BDN immediately needs WWTP capacity development plan which is adequate. Various types of technology have been widely available and ready to be used to overcome the problems of the WWTP. But on this occasion it is advisable to develop the existing WWTP facilities by adding a new WWTP unit. The first WWTP is functioned as the preliminary processing unit and the new WWTP will become an advanced processing unit. The use of a combination of anaerobic-aerobic biofilter will be relied upon to reduce pollutants that can qualify water quality standards in accordance with applicable regulations.keywords : problem identification, domestic wwtp, advanced processing